Two studies on Beethoven (Revista Argentina de Musicología, 2003)
Two independent studies. The first one takes as its point of departure a narrative conception of the musical work (Ricoeur). By means of brief analyses of 4 Beethovenian works from different periods, it tries to sketch the change undergone by the composer in his manner of presenting and resolving conflict. Beginning in the "heroic" period (Patéthique Sonata, 5th. Symphony) with simple, static conflicts the resolution of which is forced by a will alien to the conflicting materials, he arrives in the 9th Symphony to a more dynamic formulation and an immanent resolution. In such late works as the op. 131 Quartet. however, he has renounced resolution. The second study deals with the 9th Symphony, especially from the viewpoint of its reception. Taking the idea of " feast" or "festival" (as defined by sociology and anthropology) as a point of reference, it examines the variety of heterogeneous and extravagant elements that make it so unsettling. It invites the reader to listen to its incoherence, to its juxtaposition of the sublime with the grotesque, in order to loose that excessive familiarity that threatens to obliterate its subversive potential and tum it into a trivial commodity.